Liberal institutionalism theory approach in Asean’s security cooperation through regionalism - Muhammad Faiz Ramli,; Hanizah Idris, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The concepts and functions of The Association of Southeast Asian Nations (ASEAN) are different from those of other regional and international institutions, organizations, and bodies. This paper aims to analyze the concept of regionalism practiced by using the liberal institutionalism theory approach, which has successfully driven ASEAN to remain strong as an organization based on mutual relations in every aspect of politics, economy, culture, and society. This analyzes the connection between ASEAN regionalism and the liberal institutionalism theory approach, which has driven ASEAN through security cooperation until this day. ASEAN continues to operate as a regional organization that has grown from its regional cooperation through regionalism. This study discusses the various approaches on liberal institutionalism applied in interpreting ASEAN regionalism, especially in the context of economic, political, and social security cooperation. The link between globalization, the theory of liberal institutionalism, and the process of regionalism have been given significant attention, as many factors are interconnected between the subjects in the context of this study. Most of the data acquired for this study have been extracted from books, journal articles, reports by the ASEAN Secretariat, as well as library sources, in line with the need for suitable methodologies to conduct this research.